The Effect of Repeated Whole-Body Cryotherapy on Blood Thiol Status in Men Depending on Age and Physical Activity - Gabriela Wojciak; Jadwiga Szymura; Zbigniew Szygula; Joanna Gradek; Magdalena Wiecek (Rehabilitacja Medyczna)
Introduction: The aging process of society is progressing worldwide. It is associated with an increased incidence of diseases related to old age accompanied by oxidative stress. Glutathione plays a significant antioxidant role in maintaining physiological prooxidative-antioxidant balance.Objectives: The aim of the study is to assess the effects of whole-body cryotherapy (WBC) on blood thiol status of trained and untrained men depending on age.Material and methods: The study involved 20 older and 20 young healthy males. In each group, there were 10 long-distance runners (60RUN, 20RUN) and 10 untrained individuals, creating groups for comparison (60COM and 20COM). The subjects underwent 24 WBC treatments (3 min, -130C) every other day. Before and after the 1st and following the 12th and 24th WBC treatments, reduced (GSH) and oxidised glutathione (GSSG) were determined in the erythrocytes, and the oxidative stress index (GSH/GSSG) was calculated.Results: After the 1st WBC treatment, there was a significant increase in GSSG concentration for the 60RUN, 20RUN and 20COM groups, as well as a significant decrease in GSH/GSSG for 20COM. After 12 WBC treatments, the concentration of GSH in the 60COM and 20COM groups increased significantly. In contrast, a series of 24 treatments caused a significant increase in the GSH/GSSG ratio for the 60RUN group.Conclusions: A single WBC treatment affects prooxidative-antioxidant balance. Whole-bo dy cryotherapy, used in a series every other day, reduces the level of oxidative stress by increasing the concentration of GSH, especially in older people, regardless of their level of physical activity.